Effects of Canals and Levees in Everglades Ecosystems - Rebecca G. Harvey; William F. Loftus; Jennifer S. Rehage; Frank J. Mazzotti (EDIS, 2011)
WEC304, a 20-page illustrated fact sheet by Rebecca G. Harvey, William F. Loftus, Jennifer S. Rehage, and Frank J. Mazzotti, comprehensively portrays the hydrological and ecological effects of canals and levees within the EPA landscape and considers ways their impacts may be mitigated. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, December 2010.